The Passions of Chelsea Kane - Delinsky, Barbara; Simon & Schuster Audio (Firm) (New York : Simon & Schuster Audio Books, 2003)
After the death of her adoptive mother, Chelsea Kane is a woman consumed by a need to discover her natural heritage. She arrives in the New Hampshire town where she was born, aching for answers. It is while she is looking for them that she finds something quite unexpected: a love she thought she would never know.
Abridged.
Compact disc.
Producer and director, Karen Pearlman ; associate producer, Suzanne Wetzel ; abridged for audio by Jan Werner.
Read by Karen Ziemba.
Keywords: Women architects -- Fiction; Quarries and quarrying -- Fiction; Birthparents -- Fiction; New Hampshire -- Fiction; Romantic suspense